Memikat Pengunjung: Strategi Pemasaran Terkini di Happy Puppy Family Karaoke Parepare - Manuel, Semharjuno; Ogi, Yakub; Saputra, Ashari; Amelia, Lisa; RM, Saripah A (Jurnal Ilmiah Multidisiplin Amsir, 2022)
The aim of this study is to investigate the public relations marketing strategies of Happy Puppy Family Karaoke Parepare in attracting visitors. The research methodology employed is a qualitative approach, aiming to describe and explain events using facts as the basis of observation. Additionally, the researcher conducts analysis, data integration, and classification. Data collection is carried out through interviews and documentary studies. The research findings indicate that Happy Puppy Parepare employs various public relations marketing strategies to attract visitors, including corporate identity, sponsorship, community relations, publicity, and customer relations. These strategies are implemented through the stages of planning, execution, and evaluation. However, out of the 7 identified public relations marketing activities, only 4 are implemented by Happy Puppy Parepare.